MANAJEMEN PENDIDIKAN KARAKTER DI MADRASAH - Ahmad Salim (Tarbawi, 2015)
The existence of inequality of educational outcomes in terms of the behavior of graduates like brawl, corruption, free sex, drug, theft and other deviant behavior. Even some immoral allegedly perpetrated by "madrasah". Ideally, "madrasah" students have good behavior because at the school has been given the charge of educational materials more than any other institution. Seeing these problems, the government stipulates that character education to be implemented in schools. This study is feasible to manage effectively character education in "madrasah" that starts from the planning, organizing, implementing, monitoring, and evaluation. The series of management functions are carried out in sequence from one to the next, so that the expected values of the characters can be internalized in the students’life with indicator; students knowing the character, feel the character and able to do it.